Efficacy and safety of narrowband ultraviolet B therapy in psoriasis in Asian skin - Shamsuddin, Syed; Asad, Faria; Nadeem, Muhammad; Nabi, Haroon (Journal of Pakistan Association of Dermatologists, 2017)
Background Narrowband (NB) UVB phototherapy has been proven to be clearly more effective than broadband UVB and safer and/ or more practicable than psoralen-UVA in the management of psoriasis. Â Objectives To determine the efficacy and safety of narrowband UVB in chronic plaque psoriasis in Asian skin. Â Patients and methods It was a multi-centre trial. Patients suffering from chronic plaque psoriasis, between the ages of 12 and 70 years were included in the study. Minimum erythema dose was determined in each and every patient. All the patients were exposed to narrowband UVB. At each visit, PASI was determined and decision was made to increase or decrease the dose. Â Results Thirty two patients were enrolled, out of which, 28 were evaluable. Twenty three patients cleared over a period of 13.6 weeks. Five patients with poor response after 20 treatments were declared resistant. Three patients suffered from moderate erythema which settled later on. None of our patients developed painful erythema. Generalized hyperpigmentation occurred in all the patients. Â Conclusion Narrowband UVB is safe and effective in the treatment of psoriasis, but long term follow up is needed to determine its carcinogenic effects. Â